An Eclectic Framework for Grammatical Instruction in Tribal Educational Settings - B.R Aravind; S.D Srirevathi (Studies in Language, Education, and Culture (SeLEC), 2026)
This research investigation evaluates the efficacy of a novel teaching strategy by combining the “Constructivism” theory of language learning with the modern methodology known as “Principled Eclecticism” to teach tribal students the Parts of Speech (Nouns, Verbs, and Adjectives). It demonstrates how this innovative method adapts well-known writing pedagogies to the unique requirements of tribal learners, thereby addressing the difficulties that students encounter due to exposure to a foreign language. The eclectic methods used include Computer-Assisted Language Learning (CALL), Contextualised Learning, and Communicative Language Teaching (CLT). Forty Grade XIII students from the Government Tribal Residential High School in Top Sengattupatti, Tiruchirappalli, participated in a research study. The mixed-method research involved designing a lesson plan that incorporates constructivist principles alongside the application of principled eclecticism. This is achieved by categorising, selecting, and sequencing writing instruction exercises. To promote interaction and participation in writing tasks requiring contextualised focus, the term “principled” refers to coherence that repeatedly concentrates on the same formal or functional elements and arranges them sequentially. In summary, the study offers a viable way to enhance the teaching of parts of speech by creatively fusing constructivism with principled eclecticism.